Republic of Serbia : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2013)
This Selected Issues paper on Serbia's Article IV Consultation reviews the precrisis growth paradigm and its legacy vulnerabilities. The underlying growth model proved vulnerable to shocks, being associated with a high share of nontradable, low domestic savings, and a fragile external position. Convergence to EU income levels was relatively moderate. Economic growth fell following the onset of the global financial crisis and further slowed the pace of convergence. Serbia's postcrisis income gap remains larger by comparison to more advanced regional economies. Structural bottlenecks continue to undermine overall competitiveness and constrain growth potential.